The relationship between at-risk foot and all-cause and cardiovascular mortality among the population with diabetes - Wu, Zhe; Dong, Jin; Li, Meng; Chu, Chu; Wang, Bin (Frontiers in Medicine, 2025)
BackgroundDiabetic foot (DF) is a common complication among people with diabetes, typically caused by peripheral neuropathy (PN) and/or peripheral arterial disease (PAD) of the lower limbs. The existing research mainly focuses on cases of diabetic foot ulcers, while the relationship between at-risk foot and all-cause and cardiovascular mortality in the general U.S. population remains unclear.MethodsThis study utilized data from National Health and Nutrition Examination Survey (NHANES) 1999–2004 to conduct a cohort study. At-risk foot are defined as those in diabetic people who have concurrent PAD and/or PN, and without the presence of chronic ulcers in the lower extremities. Kaplan–Meier survival analysis and Multivariable Cox regression models were used to analyze the association between at-risk foot and all-cause and cardiovascular mortality, with subgroup analyses conducted.ResultsA total of 946 participants were included in the study, of which 301 had at-risk foot. The median follow-up time was 190 months. Multivariable Cox regression analysis showed that the all-cause mortality (HR: 2.050, 95% CI: 1.524, 2.758) and cardiovascular mortality (HR: 2.494, 95% CI: 1.809, 3.438) in at-risk foot people were significantly higher than in those without at-risk foot. Additionally, people with ischemic at-risk foot had a higher risk of mortality compared to those with non-ischemic neuropathic at-risk foot.ConclusionPatients with at-risk foot in the diabetic population are significantly associated with increased all-cause and cardiovascular mortality. Early diagnosis and intervention of PAD and PN in diabetes people are crucial for reducing mortality risk.